Stoichiometry of cellular and viral components in the polyomavirus middle-T antigen-tyrosine kinase complex. - Cheng, S H (1990)
Our results indicate that only one type of tyrosine kinase is present within each middle-T antigen-tyrosine kinase complex, suggesting that middle-T antigen forms separate complexes with different tyrosine kinases. Furthermore, we determined that there is only one molecule of middle-T antigen within any one of these complexes. We interpret this to mean that in any given cell, polyomavirus transformation involves, at least in part, the simultaneous deregulation of a number of separate pathways controlling cellular proliferation. Finally, we also demonstrate that the separate middle-T:pp60c-src and middle-T:pp59c-fyn complexes are each able to interact with the same cellular p81/85-kDa phosphoprotein, a possible component of the phosphatidylinositol kinase.